Hydroclimate variability of central Indo-Pacific region during the Holocene. (1st February 2021) - Chawchai, Sakonvan; Tan, Liangcheng; Löwemark, Ludvig; Wang, Hao-Cheng; Yu, Tsai-Luen; Chung, Yun-Chuan; Mii, Horng-Sheng; Liu, Guangxin; Blaauw, Maarten; Gong, Shou-Yeh; Wohlfarth, Barbara; Shen, Chuan-Chou
Abstract: Here we present a decadal-resolved hydroclimate record covering the past 11 thousand years based on δ 18 O data of three stalagmites from Klang Cave (TK) on the Thai-Malay Peninsula, southern Thailand. The δ 18 O values indicate wetter conditions/more rainfall during the early Holocene from 11 to 7 thousand years before present (kyr BP). A large increase of 2‰ in δ 18 O is observed from 7.0 to 6.0 kyr BP, indicating a millennial drying period followed by drought conditions between 6.0 and 5.2 kyr BP. After a long hiatus (5.2–2.7 kyr BP), δ 18 O data show a millennium-long trend toward dry conditions. An abrupt positive change of 0.8–1.0‰ in δ 18 O is noticed between 8.29 and 8.17 kyr BP, reflecting the 8.2-ka event; however, the amplitude of the δ 18 O shift is much smaller comparing to that of the event of 6.0–5.2 kyr BP. On orbital time-scales, the TK record agrees with insolation-dominated speleothem records in the Asian-Australian monsoon realm. Noticeable inconsistencies among records in the Southeast Asia region (between 8°N and 4°N–8°S) have been documented on multi-centennial scales. Lower δ 18 O values are likely associated with the mean position of the Intertropical Convergence Zone (ITCZ). A new reconstruction of Holocene ITCZ shifts index within the central Indo-Pacific region, based on stalagmite δ 18 O records from Klang Cave (8°N) and Liang Luar Cave (8°S), shows that the ITCZ played an important role in hydroclimate variability in the Asian-Australian monsoon regions. The southward shift of the ITCZ in the central Indo-Pacific region, controlled by the interhemispheric extratropical insolation gradient, may strongly correlate with the El Niño-Southern Oscillation (ENSO) activities in the Holocene. Highlights: Holocene stalagmite δ 18 O record of Thai-Malay Peninsula, southern Thailand. Wet conditions/strong rainfall during 11-7 kyr BP and a drying trend since 6 kyr BP. Stalagmite record of 8.2-ka event in the tropical Indo-Pacific region. A new Holocene ITCZ shift index record for the central Indo-Pacific region.